Fishing methods and fish species composition of landings in Meenkara Reservoir, Kerala - Raju, Saranya; Sandhya, K. M.; Thomas, Saly N.; Krishnan, Amrutha R.; Manojkumar, B. (Journal of the Inland Fisheries Society of India, 2022)
The present study deals with documentation of fishing methods and fish species composition of landings in the Meenkara reservoir, Kerala, India. Coracle (Parasal) was the only fishing craft and set gillnet was the main fishing gear used in the reservoir. Polyamide multifilament and monofilament gillnets of different mesh sizes (120, 150, 200, 250 and 300 mm) were predominantly used. Fish species composition of the landings comprised of 21 species belonging to 7 orders and 11 families. Family Cyprinidae was dominant followed by Cichlidae. Oreochromis niloticus was the dominant species, followed by Labeo rohita, O. mossambicus, Cirrhinus mrigala, L. catla, and Etroplus suratensis. According to the International Union for Conservation of Nature (IUCN), 2 species were Vulnerable and 2 were Near Threatened. The information generated will act as a baseline data of fisheries of the Meenkara reservoir and be useful for developing suitable strategies for proper exploitation and management of fishery in the reservoir.Key words Fishing gear; Fishing craft; Fish diversity; Meenkara Reservoir